Primary sarcomas of the pancreas: A review of 253 patients from the National Cancer Data Base. (December 2018) - Youngwirth, Linda M.; Freischlag, Kyle; Nussbaum, Daniel P.; Benrashid, Ehsan; Blazer, Dan G.
Abstract: Introduction: Primary sarcomas of the pancreas are rare, and the limited data regarding their presentation, oncologic profile, and survival have been derived from small case series. Methods: The National Cancer Data Base (1998–2012) was queried for patients with primary sarcomas of the pancreas. Demographic and clinical features at the time of diagnosis were evaluated for all patients. Subjects who underwent surgical resection were identified, and logistic regression was used to identify variables associated with resection. A Cox proportional hazards model was developed to identify factors associated with survival. Results: In total, 253 patients were identified. The mean age at diagnosis was 63 years, with tumors occurring more frequently in women (57.3%) and those of white race (79.8%). Tumors in the head of the pancreas were most common (63.3%). The mean size was 7.5 cm. Only 100 patients (39.5%) underwent resection, with younger age (OR = 0.763, p = 0.04) and smaller tumor size (OR = 0.978, p < 0.01) associated with resection. Chemotherapy and radiation therapy use were similar in patients who underwent resection and those who did not. Patients who underwent resection had a median survival of 17 months, compared to 6 months for patients who were not resected (p < 0.01). Following adjustment, only older age (HR 1.257, p = 0.03) and higher tumor grade (HR 1.997, p = 0.01) were associated with an increased risk of death in resected patients. Conclusions: Primary pancreatic sarcomas are rare and the majority of patients do not undergo resection; thus, little is known about their oncologic profile or outcomes following pancreatectomy. Patients who undergo resection have markedly improved survival; older age and higher tumor grade are associated with decreased survival.